Defect Restoration of Low‐Temperature Sol‐Gel‐Derived ZnO via Sulfur Doping for Advancing Polymeric Schottky Photodiodes. (30th May 2018) - Kim, Kyounghwan; Sim, Kyu Min; Yoon, Seongwon; Jang, Min Su; Chung, Dae Sung
Abstract: This study shows that the deep‐level defect states in sol‐gel‐derived ZnO can be efficiently restored by facile sulfur doping chemistry, wherein the +2 charged oxygen vacancies are filled with the S 2− ions brought by thiocyanate. By fabricating a solution‐processed polymeric Schottky diode with ITO/ZnO as the cathode, the synergetic effects of such defect‐restored ZnO electron selective layers are demonstrated. The decreased chemical defects and thus reduced mid‐gap states enable to not only enlarge the effective built‐in potential, which can expand the width of the depletion region, but also increase the Schottky energy barrier, which can reduce undesired dark‐current injection. As a result, the demonstrated simple‐structure blue‐selective polymeric Schottky photodiode renders near‐ideal diode operation with an ideality factor of 1.18, a noise equivalent power of 1.25 × 10 −14 W Hz −1/2, and a high peak detectivity of 2.4 × 10 13 Jones. In addition, the chemical robustness of sulfur‐doped ZnO enables exceptional device stability against air exposure as well as device‐to‐device reproducibility. Therefore, this work opens the possibility of utilizing low‐temperature sol‐gel‐derived ZnO in realizing high‐performance, stable, and reliable organic photodiodes that could be employed in the design of practical image sensors. Abstract : Synergetic effects of chemical defect restoration method of sol‐gel‐derived ZnO layer are reported. By reducing defect states of ZnO via S‐doping, built‐in potential and Schottky barrier of ZnO/polymer Schottky junction are remarkably increased, leading to enhanced depletion width and dark current injection barrier. As a result, high detectivity polymer photodiode with remarkable reliability and stability is reported.